Implementation of Education Program Marketing in Strengthening Superior School Branding (Multi-Site Study in SMPN 1 Magetan and SMPN 4 Magetan) - Esti Rachmawati; Erny Roesminingsih; Dewie Tri Wijayati Wardoyo; Amrozi Khamidi; Nunuk Hariyati (LP. Ma'arif Janggan Magetan, 2024)
Schools compete for students every new school year. Through typical school branding, they offer the advantages of the programs they have. Marketing of school programs can make the community will know about school branding, The method in this study uses a qualitative research approach. Researchers chose SMPN 1 Magetan and SMPN 4 Magetan because these two schools are favorid schools and are superior schools with various educational programs run such as the large number of extra-curriculars that can be followed by students for the development of talents and interests. Marketing of the bilingual program at SMPN 1 Magetan uses several methods, namely Word of Mouth Marketing (WoMM) by maximizing the student guardian association and Digital marketing by utilizing resources through mass media such as Facebook, WhatsApp group association. SMPN 4 Magetan conducts marketing with WoMM or word of mouth utilizing the class committee, which every PPDB is collected for the socialization of tahfidz class. SMPN 4 Magetan has SPATMA TV so that it can be used for socialization with the outside community. In addition, it also holds promotions through PAI performances.